Trail of secrets [large type] - Williams, Lacy (Wagon train matches, 2023)
"Stella is the oldest of three sisters and she's got a long history of being the one to protect and provide for her family. When a dangerous threat sent the Fairfax sisters on a wagon train journey west, Stella knew her best bet was to disguise herself as a man to keep herself and her sisters safe. Collin Mason has secrets of his own. And his family isn't short on drama either, not with his troublemaking twin and an older brother about to get hitched. But he's the only one who sees the real Stella--and that she needs help. Collin sees the vulnerability Stella tries so hard to hide. When he becomes the only one she can trust and she discovers that danger has followed her family, Stella must rely on him despite her reluctance..." -- Provided by publisher.